Infraestrutura de Investigação para a Ciência e Tecnologia da Linguagem - PORTULAN CLARIN - Branco, António; Mendes, Amália; Quaresma, Paulo (Revista da Associação Portuguesa de Linguística, 2021)
This paper presents the PORTULAN CLARIN Research Infrastructure for the Science and Technology of Language, which is part of the European research infrastructure CLARIN ERIC as its Portuguese national node, and belongs to the Portuguese National Roadmap of Research Infrastructures of Strategic Relevance. The PORTULAN CLARIN includes a helpdesk, a repository, where resources, such as corpora, lexicons and processing tools are deposited for long-term archiving and can be searched and retrieved, and a workbench, where Language Technology tools and applications are made readily available online and can be used in different types of interfaces. Its goal is to contribute to the technological development of natural languages and for their preparation for the digital age, with a special focus on the Portuguese language in all its varieties and modalities.